Colombia : Second Review Under the Stand-By Arrangement and Request for Rephasing of Purchases. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The economy has performed strongly. The government has lowered the target for the combined public sector deficit. The prospects for sustained growth over the medium term are favorable, in view of the robust growth in nonresidential investment and exports. Fiscal policy will remain on a sustainable path. Key structural reforms will move forward, once the new congress and government take office. The inflation targeting framework has provided a useful anchor for expectations and confidence. The government is developing several reforms to deepen the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet